Decompression of the Posterior Horn of the Medial Meniscus Based on Arthroscopic Findings During Deep Flexion of the Knee Joint: Resection of Osseous Bulge on the Posteromedial Femoral Condyle - Jun Suganuma, M.D.; Ryuta Mochizuki, M.D. (Arthroscopy Techniques)
In a knee with cam impingement of the posterior femoral condyle, the posterior horn of the medial meniscus (PHMM) is pinched and damaged between the medial femoral condyle (MFC) and the medial tibial plateau during deep flexion of the knee. The cam impingement is caused by an osseous bulge on the posteromedial surface of the distal femoral metaphysis and the absence of an alcove for the PHMM at the junction of the MFC and the posteromedial metaphysis of the femur. Therefore, the osseous bulge needs to be resected and the alcove needs to be restored when the PHMM is decompressed. However, it is difficult to evaluate whether the bone resection is sufficient to decompress the PHMM intraoperatively. Therefore, we developed a method to evaluate arthroscopically whether the PHMM is compressed between the MFC and the medial tibial plateau. This technique enables necessary and sufficient resection of bone tissue, regardless of the volume of the PHMM.